Perceived Accessibility of Public Transport as a Potential Indicator of Social Inclusion - Katrin Lättman; Margareta Friman; Lars E. Olsson (Social Inclusion, 2016)
Perceived accessibility has been acknowledged as an important aspect of transport policy since the 70s. Nevertheless, very few empirical studies have been conducted in this field. When aiming to improve social inclusion, by making sustainable transport modes accessible to all, it is important to understand the factors driving perceived accessibility. Unlike conventional accessibility measures, perceived accessibility focuses on the perceived possibilities and ease of engaging in preferred activities using different transport modes. We define perceived accessibility in terms of how easy it is to live a satisfactory life with the help of the transport system, which is not necessarily the same thing as the objective standard of the system. According to previous research, perceived accessibility varies with the subjectively-rated quality of the mode of transport. Thus, improvements in quality (e.g. trip planning, comfort, or safety) increase the perceived accessibility and make life easier to live using the chosen mode of transport. This study (n=750) focuses on the perceived accessibility of public transport, captured using the Perceived Accessibility Scale PAC (Lättman, Olsson, & Friman, 2015). More specifically, this study aims to determine how level of quality affects the perceived accessibility in public transport. A Conditional Process Model shows that, in addition to quality, feeling safe and frequency of travel are important predictors of perceived accessibility. Furthermore, elderly and those in their thirties report a lower level of perceived accessibility to their day-to-day activities using public transport. The basic premise of this study is that subjective experiences may be as important as objective indicators when planning and designing for socially inclusive transport systems.